PENGARUH PENERAPAN MEDIA KARTU POSITIF DAN KARTU NEGATIF PADA MATERI OPERASI HITUNG BILANGAN BULAT TERHADAP HASIL BELAJAR PESERTA DIDIK KELAS VI SDN 232 INPRES MARUSU KAB. MAROS - Masna; Nursalam; Suarti (Prodi PGMI IAI Sahid, 2024)
This study aims to find out (1) The learning outcomes of students before the application of positive card and negative card learning media on integer arithmetic operations at SDN 232 Inpres Marusu, Maros Regency, (2) Student learning outcomes after applying positive card and negative card learning media to integer arithmetic operations at SDN 232 Inpres Marusu, Maros Regency, and (3) Are there differences in learning outcomes before and after the positive card and negative card media are applied to the integer arithmetic operations sub-theme at SDN 232 Inpres Marusu. The type of research used in this research is pre-experimental with the design